Association Between Parental BMI and Offspring's Blood Pressure by Mediation Analysis: A Study Using Data From the Korean National Health and Nutrition Examination Survey - Hyowon Choi; Hunju Lee; Yeon-Soon Ahn (Korean Society for Preventive Medicine, 2023)
Objectives This study analyzed the relationship between parental body mass index (BMI; BMI_p) and hypertension in their adolescent offspring (HTN_a), focusing on the mediating effect of adolescents' BMI (BMI_a). Methods Utilizing data from the Korea National Health and Nutrition Examination Survey, including participants aged 12-18, we conducted a mediation analysis while controlling for confounding factors such as age, sex, physical activity, dietary habits, household income quartile, and parents' alcohol and smoking habits. Results The study included a total of 5731 participants, of whom 3381 and 5455 participants had data on fathers' and mothers' BMI, respectively. For adolescent systolic blood pressure (SBP_a), the father's BMI (BMI_f) had a significant total effect (β, 0.23; 95% confidence interval [CI], 0.12 to 0.34) and average controlled mediated effect (ACME) (β, 0.27; 95% CI, 0.23 to 0.32), but the average direct effect (ADE) was not significant. The mother's BMI (BMI_m) had a significant total effect (β, 0.17; 95% CI, 0.09 to 0.25), ACME (β, 0.25; 95% CI, 0.22 to 0.28) and ADE (β, -0.08; 95% CI, -0.16 to 0.00). For adolescent diastolic blood pressure, both BMI_f and BMI_m had significant ACMEs (β, 0.10; 95% CI, 0.08 to 0.12 and β, 0.09; 95% CI, 0.07 to 0.12, respectively), BMI_m had a significant ADE (β, -0.09; 95% CI, -0.16 to -0.02) but BMI_f had an insignificant ADE and total effect. Conclusions The study found that parental BMI had a significant effect on SBP_a, mediated through BMI_a. Therefore, a high BMI in parents could be a risk factor, mediated through BMI_a, for systolic hypertension in adolescents, necessitating appropriate management.